1992
DOI: 10.1017/s0041977x00003682
|View full text |Cite
|
Sign up to set email alerts
|

Hausa glottalic consonants: a laryngographic study

Abstract: The Chadic (Afroasiatic) language Hausa, spoken mainly in Nigeria and the Republic of Niger, has a series of ‘glottalic’ obstruents. This includes both ejectives ([k’], [s’] or [ts’]; orthographic κ,ts) and two other consonants which have often been described as ‘implosives’ and are represented by the IPA symbols for implosives in Hausa orthography (б,d). In addition, there is a ‘laryngealized’ palatal glide (orthographic ‘y). The description of orthographic б,das implosive has been called into question, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In his phonetic study of West African languages, Ladefoged found : 'these sounds may be incidentally implosives on some occasions, but they are always distinguished from their voiced counterparts by being laryngealised ' (1968 : 16). In a more recent instrumental study, Lindsey et al (1992) found that the implosives are typically laryngealised, and sometimes even fully glottalised, i.e. produced with the same waveform patterns as the glottal stop.…”
Section: Implosivesmentioning
confidence: 95%
“…In his phonetic study of West African languages, Ladefoged found : 'these sounds may be incidentally implosives on some occasions, but they are always distinguished from their voiced counterparts by being laryngealised ' (1968 : 16). In a more recent instrumental study, Lindsey et al (1992) found that the implosives are typically laryngealised, and sometimes even fully glottalised, i.e. produced with the same waveform patterns as the glottal stop.…”
Section: Implosivesmentioning
confidence: 95%
“…While there is some variation in the way such sounds are realized, from a phonological point of view it appears sufficient to recognize two categories of nonexplosive stops, plain (modally voiced) and laryngealized/glottalized (produced with glottal creak or glottal closure). In languages lacking a contrast between these two types, implosives may have little if any laryngealization, as in most Bantu languages, strong glottalization as in Hausa (Lindau 1984, Lindsey et al 1992, or more rarely, complete glottal closure as in Bwamu (Manessy 1960). …”
Section: Implosives and Other Nonobstruent Stopsmentioning
confidence: 99%
“…The distinction among some of these categories is subtle, but is often auditorily detectable. For example, the Xhosa implosives, including their voiceless variants, are typically produced with little or no detectable creak (Roux 1991;Michael Jessen, personal communication), while the glottalized stops of Hausa are typically creaky (Lindau 1984, Lindsey, Hayward, andHaruna 1992). Such distinctions are not contrastive in any language, as far as we know.…”
Section: Other Types Of Nonobstruent Stopsmentioning
confidence: 99%